Capacidade funcional e mediadores inflamatórios em idosas comunitárias com dor lombar - Barbara Zille de Queiroz (2012)
With increasing life expectancy, chronic-degenerative diseases and their complications become more frequent, often accompanied by pain. Low back pain is a relevant complaint, with great impact on functional performance. Increased levels of inflammatory mediators were detected in pain processes of the spine, locally and systemically. Aim: To compare plasma levels of interleukin-6 and sTNF-R1 and functionality between elderly woman with and without low back pain. Methods: Its an observational cross-sectional study conducted with a subsample of the epidemiological study Back Complaints in the Elders - BACE. IL-6 and sTNF-R1 plasma levels were measured using the ELISA method. Functional capacity was assessed by the Timed Up and Go test and gait speed; pain in the total sample, by the numeric pain scale; and the disability of the group with low back pain by Rolland Morris. Results: 213 elderly were included, aged 65 years (71.35 ± 4.76), sedentary, divided into 3 groups: I) 71 with LBP; II) 71 without LBP and reporting other body aches, III) 71 without LBP and no report of any pain in the body. The LBP group showed higher levels of sTNF-R1 (p = 0.016), and worse functional performance in the Timed Up and Go (p <0.001) and gait speed (p <0.01) compared to groups II and III, that were similar (p> 0.05). There were no differences in levels of IL-6 between groups. Conclusions: Elderly with LBP had higher plasma sTNF-R1 and worse functional performance compared with the older report other pains (not lumbar) and older without pain. Physical activity interventions are described in the literature as being associated with reduced concentrations of inflammatory cytokines, which demonstrates its clinical importance of this study for physical therapy.